Het humanisme ten einde? - Duyndam, Joachim (Tijdschrift voor theologie, 2019)
This paper reflects on Harari's criticism of humanism, eloquently articulated in his magnum opus Homo Deus. Harari sees humanism as the ideology of Western modernity, historically succeeding the religious ideologies of humankind in their previous hunter-gatherers period, that is, nature religion, which after the agricultural revolution is followed by monotheism. While monotheism supplanted the polytheisms of the nature gods, humanism declared the monotheistic God superfluous since humankind has taken their fate in their own hands. The scientific and the industrial revolutions of modernity, however, will evolve into the technological revolution that is currently going on, and which, in turn, will make most humans superfluous, according to Harari. This technological revolution of computers and robots will supersede the homo sapiens, and will result in – unfortunately, only a small number of – godlike humans (homo deus). This dreary scenario is underpinned from the basic presupposition in Homo Deus, that there is no principal difference between inorganic data processors (computers, robots) and organic ones (humans and other animals), which prepares for their possibly mutual substitution. Both are driven by algorithms, roadmaps that direct our thoughts, feelings, actions, and choices. Harari’s view challenges the assumption of the free will, by that reopening an old debate in Western philosophy and theology. However, the author of this paper defends the possibility of free will as the possible resilient and relatively autonomous response to heteronomous influences on the will. The author’s humanistic vision argues from several general experiences, such as patience, self-reflection, self-awareness, the ability to make mistakes, empathy, enjoyment, love, and last but not least: judgement, that is, the ability to apply a rule to a particular case or situation. The latter is topically demonstrated by the question whether a football referee could be replaced by a robot.